The Effect of The Free Nutritious Meal Program (MBG) on The Nutritional Status of Pregnant Women in The Service Area of The Paruga Community Health Center - Nurul Hamiah; Muammar Iksan; Darmin; Dea Zara Avila (Al-Hijrah Indonesia, 2026)
Background: Indonesia continues to face high rates of stunting and maternal malnutrition, necessitating innovative interventions. The Free Nutritious Meals Program (MBG), launched in 2024, aims to improve nutritional status among vulnerable populations, including pregnant women. Objective: To evaluate the effect of the MBG program on the nutritional status of pregnant women in the Paruga Community Health Center service area. Methods: A quasi-experimental study with 1:1 matching was conducted from April to May 2026, involving 108 pregnant women (54 intervention, 54 control) selected through proportional random sampling. Nutritional status was assessed using mid-upper arm circumference (MUAC) measurements before and after the intervention. Data were analyzed using paired and independent t-tests. Results: Within the MBG group, nutritional status improved significantly post-intervention (p<0.001), with 87% (47/54) of participants showing improvement. Although between-group comparison did not reach statistical significance (p=0.102), the MBG group demonstrated clinically meaningful improvements: normal nutritional status prevalence was higher (32.4% vs. 15.7%) and undernutrition lower (13.0% vs. 27.8%) compared to controls. Program acceptance was high, though challenges included uneven distribution across Posyandu centers and food-sharing practices. Conclusion: The MBG program shows promise in improving pregnant women's nutritional status. Strengthening distribution equity and nutrition education is recommended to maximize program impact.